2020
DOI: 10.1021/acsami.9b22056
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic and Antibacterial Ability of Cu-Doped Anatase TiO2 Thin Films: Theory and Experiment

Abstract: Multifunctional thin films which can display both photocatalytic and antibacterial activity are of great interest industrially. Here, for the first time, we have used aerosol-assisted chemical vapor deposition to deposit highly photoactive thin films of Cu-doped anatase TiO2 on glass substrates. The films displayed much enhanced photocatalytic activity relative to pure anatase and showed excellent antibacterial (vs Staphylococcus aureus and Escherichia coli) ability. Using a combination of transient absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 107 publications
5
82
1
Order By: Relevance
“…Thus, from the antibacterial activity test, it is confirmed that the Cu-TiO 2 NPs are maintaining the activity only in the UV light presence and no activity in the dark and thereby confirming for the photocatalytic activity of the synthesized particles in an externally controlled manner. Based on the literature reports with similar samples containing 5% Cu-TiO 2 nanofilms [23], ZnO NPs [24], and NiO NPs [25], we indicate that the observation of antibacterial effect for our synthesized Cu-TiO 2 NPs in the presence of UV light is due to the shattering of cell membranes by the oxidative stress [26]. Since, the treatment of Cu-TiO 2 NPs along with the UV light exposure to the bacterial cells acts in two different mechanisms, i.e.…”
Section: Antibacterial Activity Of Cu-tiomentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, from the antibacterial activity test, it is confirmed that the Cu-TiO 2 NPs are maintaining the activity only in the UV light presence and no activity in the dark and thereby confirming for the photocatalytic activity of the synthesized particles in an externally controlled manner. Based on the literature reports with similar samples containing 5% Cu-TiO 2 nanofilms [23], ZnO NPs [24], and NiO NPs [25], we indicate that the observation of antibacterial effect for our synthesized Cu-TiO 2 NPs in the presence of UV light is due to the shattering of cell membranes by the oxidative stress [26]. Since, the treatment of Cu-TiO 2 NPs along with the UV light exposure to the bacterial cells acts in two different mechanisms, i.e.…”
Section: Antibacterial Activity Of Cu-tiomentioning
confidence: 99%
“…Since, the treatment of Cu-TiO 2 NPs along with the UV light exposure to the bacterial cells acts in two different mechanisms, i.e. (1) the toxicity produced by the Cu ions (Cu 0 , Cu þ , and Cu 2þ ) against the cell walls, and (2) the absorbed energy by the TiO 2 above its bandgap initiates the formation of oxidative species that further attacks the cell's organic matter [23]. The similar other studies with that of ZnO and NiO NPs also supported for the involvement of oxidative species formed by any other means towards the reduction of bacterial cell number and thereby responsible for the maintenance of antibacterial activity [24,25].…”
Section: Antibacterial Activity Of Cu-tiomentioning
confidence: 99%
“…The energy difference between the indirect and direct band gap (at G) is <2 meV, however it is well known that this type of behaviour gives rise to enhanced exciton lifetimes such as seen in anatase TiO 2 or BiOX (X ¼ Cl, Br, I) photocatalysts. 52,53 In all three end member compounds there exists two degenerate bands at the VBM resulting in heavy and light hole effective masses. The full results of the effective mass modelling are given in the ESI in Table S7, † however herein the light effective masses will be documented, as the path of least resistance will likely be taken.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to theoretical calculations of the structure of TiO 2 itself and the doped or heterojunction system [32][33][34][35][36][37][38], scholars have also conducted numerous theoretical calculations and experiments to determine the interaction between the TiO 2 surface and water molecules, the migration mechanism of photoproduced electron-hole pairs, recombination of electron-hole pairs and other steps in the process to obtain an understanding of the mechanism and essential laws of photocatalytic water splitting [39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%